2006
DOI: 10.1074/jbc.m513511200
|View full text |Cite
|
Sign up to set email alerts
|

Lamins A and C but Not Lamin B1 Regulate Nuclear Mechanics

Abstract: Mutations in the nuclear envelope proteins lamins A and C cause a broad variety of human diseases, including Emery-Dreifuss muscular dystrophy, dilated cardiomyopathy, and Hutchinson-Gilford progeria syndrome. Cells lacking lamins A and C have reduced nuclear stiffness and increased nuclear fragility, leading to increased cell death under mechanical strain and suggesting a potential mechanism for disease. Here, we investigated the contribution of major lamin subtypes (lamins A, C, and B1) to nuclear mechanics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
646
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 629 publications
(701 citation statements)
references
References 40 publications
49
646
6
Order By: Relevance
“…Comparative studies on cells derived from the lamin A-deficient mice and lamin B1 gene trap mice showed that the A-type lamins are the principal contributors to the biophysical properties of the lamina, providing mechanical strength and stiffness to the nuclei [37]. These observations would be consistent with the notion that mutations in LMNA weaken the nucleus, making it more prone to damage arising from physical stress, such as would occur in the contracting heart or skeletal musculature.…”
Section: The A-type Laminopathiessupporting
confidence: 56%
See 1 more Smart Citation
“…Comparative studies on cells derived from the lamin A-deficient mice and lamin B1 gene trap mice showed that the A-type lamins are the principal contributors to the biophysical properties of the lamina, providing mechanical strength and stiffness to the nuclei [37]. These observations would be consistent with the notion that mutations in LMNA weaken the nucleus, making it more prone to damage arising from physical stress, such as would occur in the contracting heart or skeletal musculature.…”
Section: The A-type Laminopathiessupporting
confidence: 56%
“…However, the mechanical properties of the nuclei of Lmnb1 −/− mouse embryonic fibroblasts (MEFs) in response to defined nuclear strain were normal [37]. These experiments revealed that loss of lamin B1 may cause local disturbances in NE structure without causing generalized defects in nuclear organization, stiffness, and shape stability.…”
Section: Mice With Different Lamina Compositionsmentioning
confidence: 98%
“…It has been shown that the levels of the NE proteins lamin A and C (lamin A/C) determine the stiffness of the nucleus (20,(31)(32)(33), and that lower levels of lamin A/C facilitate cell migration through tight spaces (8,10,34). We studied the influence of lamin A/C on transmigration by varying the modulus of the NE in our model (Fig.…”
Section: Ecm Stiffness and Gap Size Modulate Nuclear Transmigrationmentioning
confidence: 99%
“…Conceptually, this work is related to modern directions towards investigating multi-cellular assemblies, monolayers and tissues [16,24,25,141]. Micropipette aspiration [142][143][144][145] has also come into use to study whole-cell mechanics by examining cellular and nuclear deformations in response to suction [146][147][148][149]. Microplates [150,151] have been employed to measure cellular deformation and elasticity in response to force.…”
Section: Introductionmentioning
confidence: 99%